История одного города - Салтыков-Щедрин Михаил Евграфович (Бриллиантовая коллекция, 2006)
Экземпляры: ДО (20191011☮) / Инвентарный номер: 57939 / Цена: 50.00 / Авт.знак: С16 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1